Tanggung Jawab Notaris Terhadap Pelaporan Akta Wasiat Secara Elektronik - Dina Sulistianingsih (CV Rewang Rencang, 2024)
The notary's responsibility in reporting wills electronically is based on the Regulation of the Minister of Law and Human Rights Number 60 of 2016. Along with the development of technology, registration of wills is now done online through the Directorate General of General Legal Administration (Dirjen AHU). The notary's obligation to register and report wills and the legal impact if the obligation is not carried out. Although a will that is not registered remains valid as an authentic deed, negligence in reporting can have implications for the degradation of the deed's evidentiary power to become a private deed. In addition, notaries who do not report wills can be subject to administrative and civil sanctions, including compensation to the injured party